Tumor grade-associated genomic mutations in Chinese patients with non-small cell lung cancer - Wang, Yang; Qin, Shilei; Liang, Yuepei; Yan, Ling; Zheng, Min; Zeng, Yanwu; Lu, Leilei (Frontiers in Oncology, 2023)
Background: Lung cancer is the most prevalent cancer worldwide. It also causes about 20% of cancer-related death in China every year. Of them, high-grade lung cancer is especially dangerous. Understanding the mechanism of high-grade lung cancer could help to develop a novel treatment for these patients. Methods: Chinese patients with lung cancer were enrolled. The tumor samples were collected by surgery or puncture and applied for next-generation sequencing. A panel of pan-cancer genes was targeted. To improve the sensitivity of detecting mutations, the sequencing depth is over 1000. Gene mutations including short-length mutations (substitution, insertion, and deletion), copy number variation, and gene fusion were called. Gene mutations within low-grade, middle-grade, and high-grade tumors with Fisher’s exact test. The enriched pathways in each grade of tumors were also inferred. Results: Of a total of 173 Chinese patients with lung cancer, 98 (56.6%) patients were female and 75 (43.4%) were male. The mean age of these patients was 56.8 years. All the patients were at the status of microsatellite stability. Most of them (66.4%) were at the early stage (Stages 0, I, and II) and had a tumor mutation burden of around 2.5 (confidence interval = [0, 48.3]). When compared to low-grade tumors, the high-grade tumor had an elevated percentage of mutations in TP53 (75.9% vs 34.4%, p = 1.86e-3) and PIK3CA (24.1% vs. 0%, p = 3.58e-3). Pathway analysis found that high-grade tumors were enriched with mutations in bacterial invasion of epithelial cells (31% vs. 0%, p = 5.8e-4), Epstein-Barr virus infection (79.3% vs. 37.5%, p = 1.72e-3), and Wnt signaling pathway (75.9% vs. 34.4%, p = 1.91e-3). High-grade tumors had a significantly higher tumor mutational burden than low-grade tumors (P-value=0.0017). Actionable mutations with high-level evidence were lower in high-grade tumors. Conclusion: High-grade tumors from lung cancer patients could be more affected by bacteria and Epstein-Barr virus than low-grade tumors, and they were specially mutated in TP53 and PIK3CA. Patients with high-grade tumors could benefit more from immunotherapy.